Cardiac troponins and NT-proBNP in the forensic setting: Overview of sampling site, postmortem interval, cardiopulmonary resuscitation, and review of the literature. (January 2018) - Palmiere, Cristian; Tettamanti, Camilla; Bonsignore, Alessandro; De Stefano, Francesco; Vanhaebost, Jessica; Rousseau, Guillaume; Scarpelli, Maria Pia; Bardy, Daniel
Highlights: Cardiac troponins and NT-proBNP may be reliably measured in postmortem serum from femoral blood. Postmortem intervals over 48 h may cause increased levels of cardiac troponins in postmortem serum from femoral blood. Cardiopulmonary resuscitation does not influence cardiac troponins and NT-proBNP levels. Abstract: The possible use of biochemical markers in the postmortem diagnosis of myocardial ischemia is well known in the forensic setting, though several issues have limited its widespread adoption. The study presented herein focuses of N-terminal pro-B-type natriuretic peptide, troponin T, and troponin I, and the possible influence due to sampling site chosen, postmortem interval elapsed, and cardiopulmonary resuscitation attempts. Comparisons were performed between antemortem serum levels of these markers and postmortem levels measured in pericardial fluid and postmortem serum samples obtained from different sampling sites (n = 16). Levels of these markers were also compared in cases characterized by various postmortem intervals (n = 48, consisting of 24 ischemic heart disease cases and 24 controls) as well as in cases with and without cardiopulmonary resuscitation (n = 22, consisting of 14 cases of hanging and 8 cases of drug intoxication). Our results indicate that N-terminal pro-B-type natriuretic peptide, troponin T, and troponin I values determined in postmortem serum from femoral blood (collected up to 24 h after death) do not differ significantly from those measured in venous blood antemortem serum samples (collected at the upper limbs). In addition, our results reveal that the time elapsed after death should always be taken into consideration when cardiac troponins are measured in postmortem samples. Lastly, our findings reveal the absence of statistically significant differences between levels of the tested biomarkers (in postmortem serum from femoral blood) in cases without cardiopulmonary resuscitation compared to cases with cardiopulmonary resuscitation (at least for postmortem intervals up to 24 h).